2015
DOI: 10.1002/lary.25043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of voice outcomes after trial and long‐term vocal fold augmentation in vocal fold atrophy

Abstract: This is the first study to provide comparative voice outcomes using both trial VFI and long-term augmentation for vocal fold atrophy. Additional critical evaluation of the value of trial VFI for vocal fold atrophy patients is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
2
24
2
1
Order By: Relevance
“…They defined a successful treatment effect as a decrease of at least 5 on the VHI‐10. Approximately 45% of their patients reported improvement following IA compared to 20% in the current study. Thirty‐three percent of patients in that study who reported improvement following IA subsequently returned to have a more permanent procedure, compared to only one patient in our study.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…They defined a successful treatment effect as a decrease of at least 5 on the VHI‐10. Approximately 45% of their patients reported improvement following IA compared to 20% in the current study. Thirty‐three percent of patients in that study who reported improvement following IA subsequently returned to have a more permanent procedure, compared to only one patient in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Another study examined successful treatment effects following trial injection and subsequent long‐term treatment. They defined a successful treatment effect as a decrease of at least 5 on the VHI‐10.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations